On the Connections Between Item Response Theory and Classical Test Theory: A Note on True Score Evaluation for Polytomous Items via Item Response Modeling. (December 2019) - Raykov, Tenko; Dimitrov, Dimiter M.; Marcoulides, George A.; Harrison, Michael
This note highlights and illustrates the links between item response theory and classical test theory in the context of polytomous items. An item response modeling procedure is discussed that can be used for point and interval estimation of the individual true score on any item in a measuring instrument or item set following the popular and widely applicable graded response model. The method contributes to the body of research on the relationships between classical test theory and item response theory and is illustrated on empirical data.